Development of wireless sensor node hardware for large-area capacitive strain monitoring. (20th November 2018) - Jeong, Jong-Hyun; Xu, Jian; Jo, Hongki; Li, Jian; Kong, Xiangxiong; Collins, William; Bennett, Caroline; Laflamme, Simon
Abstract: Conventional resistive-type strain sensing methods have limitations in large-area sensing due to their relatively small size. The soft elastomeric capacitive (SEC) sensor is a capacitance-based stretchable electronic strain sensor, which has shown distinct advantages for mesoscale sensing over conventional strain-based structural health monitoring (SHM) due to its wide surface coverage capability. While recent advances in wireless sensor technologies have provided an attractive alternative to wired and centralized SHM, the capacitive strain sensing methods have not benefitted from the wireless approaches due to the lack of appropriate hardware element. This study develops a wireless sensor board to use the SEC sensor in combination with a wireless sensor network for SHM by addressing key implementation challenges. An alternating current (AC)-based De-Sauty Wheatstone bridge circuit is employed, converting dynamic capacitance variation from the SEC sensor into analog voltage signal. A high-precision bridge balancer and two-step signal amplifiers are implemented to effectively apply for low-level structural strain vibrations. An amplitude modulation-demodulator has been designed to extract the baseband signal (i.e. strain signal) from the carrier signal (i.e. AC excitation for the Wheatstone bridge). And a dual-step shunt calibrator has been proposed to remove the parasitic capacitance effect of lead wires during on-board calibration process. The performances of the sensor board developed in this study have been validated via a series of lab tests, outperforming a conventional wired capacitance measurement system.